Baby boomers, age, and beauty - Woodspring, Naomi (Emerald Publishing Limited, 2018)
This book is a rich exploration of the baby boomers - those coming of age in the sixties and now entering old age - the influences that have shaped how they perceive ageing appearance, how they define ageing and beauty, and the meaning of appearance, beauty, and identity. The book draws from a variety of sources from ageing research, history and gender studies and a diverse group of interviewees. The longevity revolution and shifting notions of identity coalesce as older women and men seek to find new modes of self-presentation as they age. Ageing is a profoundly embodied process, yet older people's concerns about appearance and beauty is perceived, by many, as trivial or a function of consumer society. Investigating notions of appearance and beauty as a core human concern, the author explores Western cultural notions of beauty. What then is beauty in old age? Is it even a possibility given the history of youth and aesthetic preference? The book seeks to bring forward ideas of age and beauty as defined by baby boomers, how they see themselves and how they are seen.
Includes bibliographical references and index.
Print version record
Keywords: Aging -- Psychological aspects; Aging -- Social aspects; Baby boom generation; Social Science, Gerontology; Sociology: family & relationships